PERAN BUMDES DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DAERAH PEDESAAN (STUDI KASUS DESA SIPODECENG KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG) - Bahruddin, Bahruddin; Syukri, Fitriyani; Abbas, Nur Asrah (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
National development intends to create a just and prosperous society in accordance with the mandate of Pancasila and the Constitution of the Republic of Indonesia. This research aims to find out the role and problem of BUMDes Padaidi in improving the economy of sipodeceng village community. The data collection techniques used in this study are interviews, observations and documentation. Data analysis techniques in this research use qualitative descriptive analysis. The results showed that the role of BUMDes Padaidi in Sipodeceng Village has not had an impact on the overall economy of the community, which only includes BUMDes members. This is because human resources are still low and there is no socialization of Bumdes and existing business units.